Concomitant methimazole-induced agranulocytosis and cholestatic jaundice in a young woman. Issue 8 (25th August 2022) - Alcorn, Chris; Subarajan, Prathayini; Anderson, Jay
Abstract : A woman in her 30s presented to the emergency department with new-onset sore throat and fever. She had recently been diagnosed with Graves' disease 3 months prior. As a result, she was initiated on atenolol and methimazole for management. Her methimazole dosing had been stable at 15 mg daily for the month prior to presentation. Investigation revealed severe neutropenia and jaundice. She was found to have concomitant agranulocytosis and cholestatic jaundice secondary to methimazole. Methimazole was discontinued on admission and the patient received granulocyte colony-stimulating factor for an absolute neutrophil count (ANC) of zero. She was placed on broad-spectrum antibiotics and intravenous steroids for epiglottic and supraglottic oedema noted on bedside laryngoscopy. ANC and bilirubin improved over a 2-week hospital course. She was discharged on a temporary regimen of propranolol, dexamethasone and potassium iodide until she was able to undergo successful thyroidectomy for definitive management of Graves' disease outpatient.